Strategi Guru dalam Mencegah Budaya Pacaran di Sekolah Berbasis Tahfiz: Pendekatan Pendidikan Karakter Islami - Nurdiani, Nurdiani; Mardhiah, Ainal; Hayati, Hayati; Masbur, Masbur (LaKaspia, 2025)
The culture of teenage dating presents a significant challenge in shaping students’ character, especially within tahfiz-based schools that combine Islamic education and the national curriculum. This phenomenon has become a serious concern for Islamic educational institutions seeking to nurture morally grounded youth amid increasing digital exposure. This study aims to explore the strategies employed by teachers to prevent dating culture in Islamic boarding schools. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving all teachers. The findings reveal that prevention strategies are implemented in three stages: planning based on the values of iffah (self-restraint) and haya’ (modesty), implementation through daily religious routines, teacher role modeling, and social supervision, and addressing challenges such as digital media influence and limited after-hours monitoring. This study underscores the importance of integrating Islamic character education with context-sensitive pedagogical approaches in shaping adolescent behavior. It contributes to the development of character-building models responsive to the challenges of the digital age. Abstrak Budaya pacaran di kalangan remaja merupakan tantangan serius dalam pembinaan karakter siswa, terlebih di sekolah berbasis tahfiz yang mengintegrasikan pendidikan agama dan kurikulum nasional. Fenomena ini menjadi perhatian khusus bagi lembaga pendidikan Islam dalam membentuk generasi berakhlak mulia di tengah arus digitalisasi. Penelitian ini bertujuan untuk mengkaji strategi guru dalam mencegah budaya pacaran di lingkungan sekolah tahfiz. Dengan menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi terhadap seluruh guru. Hasil penelitian menunjukkan bahwa strategi pencegahan dilaksanakan melalui tiga tahap: perencanaan berbasis nilai iffah dan haya’, implementasi melalui pembiasaan ibadah, keteladanan guru, dan pengawasan sosial, serta penanganan kendala yang mencakup pengaruh media digital dan keterbatasan pengawasan di luar jam sekolah. Studi ini menegaskan pentingnya integrasi antara pendidikan karakter Islami dan pendekatan pedagogis yang kontekstual dalam membentuk perilaku remaja. Penelitian ini memberikan kontribusi bagi pengembangan model pembinaan karakter yang responsif terhadap tantangan era digital.